NEOPHRAZEOLOGICAL UNITS WITH ONOMASTIC COMPONENTS IN RUSSIAN, ENGLISH, AND UZBEK MEDIA TEXTS: A COMPARATIVE ANALYSIS - Shakhsanam Niyazmetova (Modern American Journals, 2025)
This article examines neophrazeological units with an onomastic component in the modern media discourse of Russian, English, and Uzbek. A comparative analysis reveals the structural and semantic features of such units, with particular focus on the mechanisms of phraseologization and onomastic markedness in media speech. The study is based on materials from recent print and online media.
Keywords: Neophrazeologisms, onomastics, media discourse, phraseological innovation, proper names, mass media, cultural semantics.